A simple strategy for the synthesis of well-defined bassanite nanorods1. Issue 20 (28th May 2015) - Tritschler, U.; Kellermeier, M.; Debus, C.; Kempter, A.; Cölfen, H.
<x xml:space="preserve">Abstract</x> Quenching of calcium sulfate solutions into organic solvents is a convenient method to produce uniform nanoparticles of bassanite, a metastable but industrially important phase.